A fresh look at the costs of non-fatal consumer product injuries - Lawrence, B.; Spicer, R.; Miller, Ted (B M J Group, 2015)
© 2015, BMJ Publishing Group. All rights reserved. Background: Products under the purview of the Consumer Product Safety Commission are involved in a large share of injuries and injury costs in the USA. Methods This study analyses incidence data from the National Electronic Injury Surveillance System (NEISS) and cost data based on the Injury Cost Model, integrated with the NEISS. We examined the magnitude of nonfatal consumer product related injury, the distribution of products involved in these injuries and the cost of these injuries. We compared these findings with an earlier identical study from 2000.Results: In 2008–2010, 43.8% of the annual 30.4 million non-fatal injuries treated in hospital emergency departments involved consumer products. Of these consumer product related injuries, in 2009–2010, just three product groups accounted for 77% of the $909 billion annual cost: sports and recreation; home structures and construction materials; and home furnishings and fixtures. Sports and recreation was a leading cause of injury costs among 5–24-year-olds, particularly football, basketball, bicycling, baseball/ softball and soccer. Since 1996, football surpassed basketball in becoming the number one cause of injury costs for children aged 10–19 years and the fifth ranked cause of product related injury costs overall. Among those over age 30 years, stairs and floors were a leading cause of consumer product related injury costs, in particular among those over age 70 years where they were responsible for over one-fifth of costs.Conclusions: The findings of this study highlight priority areas for intervention and generate questions for future research.